Penerapan Media Pembelajaran Video Animasi Bilingual Untuk Meningkatkan Kemampuan Bahasa Inggris Siswa Sekolah Dasar - Listia, Dian; Shabhira, Helmita Hana; Jinan, Nadia Naila; Arifah, Siti Lilik Ulya; Ginawati, Nurul Hidayah Tri; Fitammami, Vrida; Widagdo, Arif (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The advancement of digital technology has opened various opportunities for the development of innovative learning media, one of which is bilingual instructional media based on animated videos. This study aims to examine the concept of bilingual learning media, digital applications that can be used in its design, and effective implementation strategies to improve English language skills among elementary school students. This research was conducted using a descriptive qualitative approach through a literature review method from various relevant sources, including journals, articles, and books. The results show that bilingual learning media based on animated videos can enhance student engagement, motivation, and understanding of learning materials, particularly in English language instruction. This media presents material both visually and auditorily in two languages, Indonesian and English, simultaneously, thus strengthening interlingual connections and accelerating vocabulary acquisition. Applications such as Canva, Animaker, Powtoon, and Toonly have proven effective in supporting the design process of this media. Recommended design strategies include selecting contextual content, integrating cultural values, and utilizing engaging animations and audio. Therefore, this media serves as a potential alternative to create interactive, enjoyable, and meaningful learning experiences.